Electrical Conductivity, Selective Adhesion, and Biocompatibility in Bacteria‐Inspired Peptide–Metal Self‐Supporting Nanocomposites. Issue 10 (15th January 2019) - Guterman, Tom; Ing, Nicole L.; Fleischer, Sharon; Rehak, Pavel; Basavalingappa, Vasantha; Hunashal, Yamanappa; Dongre, Ramachandra; Raghothama, Srinivasarao; Král, Petr; Dvir, Tal; Hochbaum, Allon I.; Gazit, Ehud
Abstract: Bacterial type IV pili (T4P) are polymeric protein nanofibers that have diverse biological roles. Their unique physicochemical properties mark them as a candidate biomaterial for various applications, yet difficulties in producing native T4P hinder their utilization. Recent effort to mimic the T4P of the metal‐reducing Geobacter sulfurreducens bacterium led to the design of synthetic peptide building blocks, which self‐assemble into T4P‐like nanofibers. Here, it is reported that the T4P‐like peptide nanofibers efficiently bind metal oxide particles and reduce Au ions analogously to their native counterparts, and thus give rise to versatile and multifunctional peptide–metal nanocomposites. Focusing on the interaction with Au ions, a combination of experimental and computational methods provides mechanistic insight into the formation of an exceptionally dense Au nanoparticle (AuNP) decoration of the nanofibers. Characterization of the thus‐formed peptide–AuNPs nanocomposite reveals enhanced thermal stability, electrical conductivity from the single‐fiber level up, and substrate‐selective adhesion. Exploring its potential applications, it is demonstrated that the peptide–AuNPs nanocomposite can act as a reusable catalytic coating or form self‐supporting immersible films of desired shapes. The films scaffold the assembly of cardiac cells into synchronized patches, and present static charge detection capabilities at the macroscale. The study presents a novel T4P‐inspired biometallic material. Abstract : Inspired by bacterial metal‐binding protein nanofibers, nanocomposites are fabricated from mimetic self‐assembled peptide nanofibers and metallic moieties. Experimental and computational methods show how reduction of ionic Au by the nanofibers leads to their exceptionally dense decoration by gold nanoparticles. The thus‐formed nanocomposite forms a catalytic coating, or immersible self‐supporting films for cardiac patch assembly and static charge detection.